SISTEM PENYELENGGARAAN JAMINAN PRODUK HALAL PADA PELAKU USAHA DI PROVINSI BANTEN - Fatima, Nadia (Jurnal Silatene Sosial Humaniora, 2024)
Abstract The enactment of Law Number 33 of 2014 concerning Halal Product Guarantees changed the halal product guarantee system which was previously voluntary to become mandatory for business actors. The purpose of this Law is to provide legal certainty regarding the halalness of a product circulating in the community. Apart from that, it also creates a sense of security and public trust in the products available. Policies regarding halal products can be determined by regions as a potential to be able to mobilize local products that can compete with products at home and abroad. This research aims to find out and analyze how the Halal Product Guarantee Implementation System is for business actors in Banten Province. The research method used is qualitative. The results of research using the Edward III policy implementation model approach show that the Halal Product Guarantee Implementation System for business actors in Banten Province is still not running well. Campaign methods and socialization of mandatory halal policies in October 2024 have not been carried out routinely. Business actors have difficulty finding halal raw materials on the market. The number of members of the Halal Task Force in Banten Province is insufficient, there have been policy changes regarding the implementation of halal product guarantees through Law Number 6 of 2003 concerning the Determination of Perpu Number 2 of 2022 concerning Job Creation. The implementation of BPJPH service rates is quite expensi for small businesses. The Halal Certificate registration procedure is quite long and complicated.